PENERAPAN LOGIKA FUZZY UNTUK SISTEM REKOMENDASI BERBASIS M-COMMERCE - Beni Widiawan; I Putu Dody Lesmana; Ronny Fernando (Jurnal Teknologi Informasi dan Terapan, 2019)
Smartphones and tablets at this time became a popular gadgets and much liked by the community. Two of these gadgets have a wide range of brands and specifications. Many people who choose and buy two of these gadgets from the gadget specification and not a few of them who do not understand about the specifications owned two of these gadgets. Recommendation system is a system that can allow shoppers to assist in selecting a gadget based on the specifications of the gadgets owned. This system also can help buyers who do not understand about the gadget specification for the system made using the model Tahani Fuzzy Logic, Fuzzy Logic is a method that mimics human thinking by using the concept of vagueness nature of a value, so with the method of this system is expected to facilitate and can well understood by the buyer. This recommendation is made in the system in M - Commerce websites in order to facilitate buyers to access the system anywhere, anytime.